Lightning Protection Improvement and Economic Evaluation of Thailand’s 24 kV Distribution Line Based on Difference in Grounding Distance of Overhead Ground Wire - Pornchai Sestasombut; Atthapol Ngaopitakkul (Mathematical Problems in Engineering, 2021)
This study determines the voltage across insulators after a direct lightning strike to an overhead ground wire on a 24 kV pole structure for different grounding distances of overhead ground wire, to calculate the maximum ground resistance required to avoid disruption of the distribution line system using ATP-EMTP software. The results show that when a 40 kA lightning current, the average lightning current in Thailand, strikes a 24 kV pole structure, the maximum ground resistance should not exceed 4 Ω for a 40 m grounding distance of overhead ground wire, based on an existing critical insulator flashover of 205 kV. However, because the average ground resistance in Thailand is approximately 10 Ω, this study proposes increasing the insulation level from 205 kV to 300 kV to reduce the likelihood of power outage. The cost-effectiveness of such an investment is assessed in terms of net present value (NPV), internal rate of return (IRR), profitability index (PI), and discounted payback period (DPP) using existing economic tools. Results show that when the critical insulator flashover is increased from 205 kV to 300 kV for a 40 m grounding distance of overhead ground wire, the project is likely to have a DPP of 15.12 years, NPV of 143,321.87 USD, IRR of 12%, and PI of 1.15. On the other hand, grounding distances greater than 40 m for overhead ground wire result in negative NPV, although the back flashover rate can be reduced by 1.51–5.71% with grounding distances of 80–200 m compared to the situation in the absence of grounding.
Keywords: Lightning and Electromagnetic Phenomena; Electrical Fault Detection and Protection; Thermal Analysis in Power Transmission